IMPLEMENTASI PEMUNGUTAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN (PBB-P2) SEBAGAI PENDAPATAN ASLI DAERAH DI DESA SUNGAI DANAU - Muhammad Al Donie; Syaiful Hifni (Universitas Lambung Mangkurat, 2020)
This research was conducted with the aim of knowing about the implementation of the collection of Rural and Urban Land and Building Tax (PBB-P2) which was applied in Sungai Danau Village, in recent years there has been a considerable decline in Regional Original Income (PAD) from PBB-P2 receipts. This is because the collection procedures are still not good from the local government, the lack of socialization/directions given to collectors in each village and to taxpayers so that it has an impact on regional income itself and as if taxpayers are given the freedom to pay or not their obligations. because there is no firm action for taxes owed up to 5 years and above.